High pressure liquid chromatographic assay of mephenoxalone - Rollas, Sevim (Marmara Pharmaceutical Journal, 1987)
In this paper, a high pressure liquid chromatographic method was developed for the determination of mephenoxalone using clopamide as an internal standart.